Influence of pH, bleaching agents, and acid etching on surface wear of bovine enamel - Ana Flávia Soares; Juliana Fraga Soares Bombonatti; Marina Studart Alencar; Elaine Cristina Consolmagno; Heitor Marques Honório; Rafael Francisco Lia Mondelli (Journal of Applied Oral Science, 2016)
ABSTRACT Development of new materials for tooth bleaching justifies the need for studies to evaluate the changes in the enamel surface caused by different bleaching protocols. Objective The aim of this study was to evaluate the bovine dental enamel wear in function of different bleaching gel protocols, acid etching and pH variation. Material and Methods Sixty fragments of bovine teeth were cut, obtaining a control and test areas. In the test area, one half received etching followed by a bleaching gel application, and the other half, only the bleaching gel. The fragments were randomly divided into six groups (n=10), each one received one bleaching session with five hydrogen peroxide gel applications of 8 min, activated with hybrid light, diode laser/blue LED (HL) or diode laser/violet LED (VHL) (experimental): Control (C); 35% Total Blanc Office (TBO35HL); 35% Lase Peroxide Sensy (LPS35HL); 25% Lase Peroxide Sensy II (LPS25HL); 15% Lase Peroxide Lite (LPL15HL); and 10% hydrogen peroxide (experimental) (EXP10VHL). pH values were determined by a pHmeter at the initial and final time periods. Specimens were stored, subjected to simulated brushing cycles, and the superficial wear was determined (μm). ANOVA and Tukey´s tests were applied (α=0.05). Results The pH showed a slight decrease, except for Group LPL15HL. Group LPS25HL showed the highest degree of wear, with and without etching. Conclusion There was a decrease from the initial to the final pH. Different bleaching gels were able to increase the surface wear values after simulated brushing. Acid etching before bleaching increased surface wear values in all groups.